eIF4AII is dispensable for miRNA-mediated gene silencing - Galicia-Vázquez, Gabriela (RNA, 2015)
MicroRNAs (miRNAs) are short noncoding RNAs that regulate gene expression through partial complementary base-pairing to the 3′ untranslated region (UTR) of target mRNAs. Inhibition of translation initiation has been identified as an early event of miRNA-mediated gene repression, but the underlying mechanistic details of this process are not well understood. Recently, eukaryotic initiation factor (eIF) 4AII was identified as a critical modulator of miRNA activity with depletion of this factor alleviating miRNA-mediated gene repression. Using the CRISPR/Cas9-editing system, we generated a novel cell line in which expression of eIF4AII was eliminated. The absence of eIF4AII does not affect cell viability, proliferation, or global mRNA translation. Importantly, we show that eIF4AII is dispensable for miRNA-mediated gene silencing.